Materiality of Air (University of Exeter Press, 2025)
Exploring air, airborne phenomena, and elemental representation, this book dissects the materiality of air, which comes to the fore ever more vigorously given the ongoing environmental and health crises. Understanding air’s materiality is essential to outlining clear solutions to the current challenges and to generating new meanings of what constitutes an environmentally safe and healthy future. The dual nature of air makes it a rich field for metaphor and a potent subject to think with: as space that contains and engages with other elements, particles, and beings; and as matter that moves, envelopes, and penetrates objects, spaces, and time.